Diabetes, glaucoma, sex, and cataract: analysis of combined data from two case control studies. Issue 1 (January 1993) - Harding, J J; Egerton, M; van Heyningen, R; Harding, R S
Abstract : Data from two case control studies in Oxfordshire were combined and analysed. The combined study covered 1940 subjects, 723 cases, and 1217 controls, between the ages of 50 and 79 with a response rate of 97% for cases and 94% for controls. Diabetes was shown to be a powerful and highly significant risk factor for cataract with a relative risk of 5.04. More than 11% of cataracts in Oxfordshire are attributable to diabetes. The relative risk did not increase significantly with age within the range 50 to 79 years but was higher in females than in males. For females with diabetes the relative risk was 7.85 with 95% confidence interval from 4.30 to 14.3 compared with 3.42 with confidence interval from 2.05 to 5.71 for males with diabetes. Diabetes remained a powerful risk factor when other identified risk factors had been controlled for. No known mechanism for the development of diabetic complications provides an explanation for the excess risk in females. Combination of the two studies led to better estimates of the relative risk of glaucoma as a risk factor for cataract (3.96 with 95% confidence interval from 2.35 to 6.68). The relative risk appeared to be greater in women than in men but this difference was not statistically significant. There was no significant change in risk with age. Glaucoma is a powerful and independent risk factor for cataract in both sexes and may be responsible for 5% of all cataracts in our area.